Advanced remote care for heart failure in times of COVID-19 using an implantable pulmonary artery pressure sensor: the new normal. (23rd December 2020) - Bayes-Genis, Antoni; Codina, Pau; Abdul-Jawad Altisent, Omar; Santiago, Evelyn; Domingo, Mar; Cediel, Germán; Spitaleri, Giosafat; Lupón, Josep
Abstract: Heart failure (HF) is a major public health problem and a leading cause of hospitalization in western countries. Over the past decades, the goal has been to find the best method for monitoring congestive symptoms to prevent hospitalizations. Addressing this task through regular physician visits, blood tests, and imaging has proven insufficient for optimal control and has not decreased enough HF-related hospitalization rates. In recent years, new devices have been developed for this reason and CardioMEMS is one of the therapeutic monitoring options. CardioMEMS has shown to be effective in preventing and reducing HF hospitalizations in patients both with HF with reduced ejection fraction and HF with preserved ejection fraction. CardioMEMS' versatility has made it a great option for pulmonary artery pressure monitoring, both during the coronavirus disease-19 (COVID-19) pandemic and when the clinic visits have (partially) resumed. CardioMEMS is the remote haemodynamic monitoring system with the most evidence-driven efficacy, and COVID-19 has put it in the spot as a centre-stage technology for HF monitoring. In a few months of the COVID-19 epidemic, CardioMEMS has grown to maturity, making it the new normal for high-quality, high-value remote HF care.